2021
DOI: 10.1073/pnas.2107220118
|View full text |Cite
|
Sign up to set email alerts
|

Trident cold atmospheric plasma blocks three cancer survival pathways to overcome therapy resistance

Abstract: Therapy resistance is responsible for most cancer-related death and is mediated by the unique ability of cancer cells to leverage metabolic conditions, signaling molecules, redox status, and other pathways for their survival. Interestingly, many cancer survival pathways are susceptible to disturbances in cellular reactive oxygen species (ROS) and may therefore be disrupted by exogenous ROS. Here, we explore whether trident cold atmospheric plasma (Tri-CAP), a gas discharge with exceptionally low-level ROS, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Also other cell lines were found before to be more sensitive to He/O 2 than He direct plasma jet treatment 137 . Direct Ar plasma jet treatment of breast cancer cell lines was also reported in various studies 72,138–146 . With regard to plasma jets, one study compared nitrogen (N 2 ) against humid nitrogen (N 2 /H 2 O) and found the latter to be significantly more toxic than the former 147 .…”
Section: Plasma Breast Cancer Treatment and Mechanism Of Actionmentioning
confidence: 87%
See 2 more Smart Citations
“…Also other cell lines were found before to be more sensitive to He/O 2 than He direct plasma jet treatment 137 . Direct Ar plasma jet treatment of breast cancer cell lines was also reported in various studies 72,138–146 . With regard to plasma jets, one study compared nitrogen (N 2 ) against humid nitrogen (N 2 /H 2 O) and found the latter to be significantly more toxic than the former 147 .…”
Section: Plasma Breast Cancer Treatment and Mechanism Of Actionmentioning
confidence: 87%
“… 137 Direct Ar plasma jet treatment of breast cancer cell lines was also reported in various studies. 72 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 With regard to plasma jets, one study compared nitrogen (N 2 ) against humid nitrogen (N 2 /H 2 O) and found the latter to be significantly more toxic than the former. 147 This can be explained based on earlier findings identifying a critical role of humidity in the feed but not in ambient air.…”
Section: Plasma Breast Cancer Treatment and Mechanism Of Actionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specific techniques of CAP administration have been employed in the treatment of this disease. In an experimental animal model of resistant CML, the authors considered whether trident cold atmospheric plasma (Tri-CAP), a CAP with extremely low concentration of ROS, could block different survival system pathways [ 78 ]. They showed that Tri-CAP disturbed the CML survival signaling involved in glycolysis, redox deregulation, and the AKT/mTOR/HIF-1α pathway.…”
Section: Cap and Hematological Malignanciesmentioning
confidence: 99%
“…The possibility of utilizing Tri-CAP in CML patients was reported in that study. The technique might be extracorporeal for hematopoietic stem cell transplant or transdermal administration, or by its stimulated solution for infusion treatment [ 78 ]. In addition, Tri-CAP might represent a powerful approach in CML patients, especially in overwhelming chemoresistance.…”
Section: Cap and Hematological Malignanciesmentioning
confidence: 99%